Evolusi Diagnostik Sifilis Menggunakan PCR: Komparasi Metode Pemeriksaan di Indonesia dan Luar Negeri Dalam Rentang Tahun 2015-2026 - Jesslyn Widya Salim; Sara A. J. Simanullang; Kasamira S. U. Sau; Joy Miracle Tumigolung Kawer; Maroloan Aruan (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Syphilis is a sexually transmitted disease that still has a high number of cases so it is still included in the global problem, this disease is caused by Treponema pallidum, in detecting syphilis the method that is widely used is the serological test as the main test in its detection, but because syphilis can spread quickly and easily undetected, a more accurate and sensitive method is needed. The method is a molecular method, namely Polymerase Chain Reaction (PCR), this method has high sensitivity and specificity so it can be used to detect syphilis. Indonesia is one of the countries that has a high rate of syphilis cases so the PCR method is needed to help in syphilis detection, but it should be noted that PCR is not cheap and easy so its spread and development in Indonesia must be considered by comparing it with existing data abroad or internationally. The method used is a systematic literature review (SLR) which is by collecting original research articles from various journal sources such as PubMed, Google Scholar, ScienceDirect, and other journal sources that have the keywords